إعداد المعجم المصاحب (العربي – الإندونيسي – الجاوي) لكتاب آداب العالم والمتعلم للشيخ هاشم أشعري بالتطبيق في المعهد الفتح كديري - Moh. Sholeh Afyuddin; Fina Maulidah Kamilah (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2022)
Based on the results of the needs analysis conducted by the researchers at Pesantren Pelajar Al-Fath Kediri, it was found that there was a need for a companion dictionary. The researchers believe that a companion dictionary containing three languages ​​(Indonesian-Arabic-Javanese) will be able to help santri to overcome their problems in understanding the lessons presented by teachers. Learning at this pesantren uses Javanese translation, that is, the teacher reads or translates the books using Javanese translation (pegon) then he adds explanations in official Indonesian. The students copy that translation as well as the teacher's. The researchers found that most of the santri did not master that Javanese translation well, because they have different ethnic backgrounds and because that Javanese language is not be used in their daily communication, so it become foreign for them. Because of that, the students (santri) had difficulties, especially when they were going to re-study the book independently. This study uses the Research and Development method with six steps from Borg and Gall. The samples are the students at Pesantren Pelajar Al-Fath Kediri, grade 3, academic year 2020/2021. The research problems are: 1) How to make a companion dictionary (Arabic-Indonesian-Javanese) for the book Adab al-Alim Wa al-Muta'allim by Sheikh Hasyim Asy'ari, being applied to the Pesantren Pelajar Al-Fath Kediri? 2) Howa the effectiveness of using that companion dictionary (Arabic-Indonesian-Javanese) for the book Adab al-Alim Wa al-Muta'allim by Sheikh Hasyim Asy'ari, by being applied to Pesantren Pelajar Al-Fath Kediri? The result of this research is the companion dictionary for the book Adab al-Alim Wa al-Muta'allim by Sheikh Hasyim Asy'ari. Based on the assessment of dictionary content experts, this companion dictionary has a high level of quality with a percentage of 86.6%. While the assessment of the design expert is 77.6%. The test results using the T-test which shows the calculation of the value of sig (2-tailed) is 0.00 less than 0.05. This shows that the use of this companion dictionary is effective. This dictionary will contribute in development of lexicography field related to the three languages, and will assist students in independent study to understand the translation dictated in Javanese, considering that most students do not improve Javanese.